Pemberdayaan Masyarakat melalui Inovasi Biopori Galon Bekas untuk Mengurangi Timbulan Sampah Organik - Febryna Dhea Nur Ananda Ananda; Olifia Eka Putri Saktiyani; Zhilzian Putra Purnomo; Sugianto; Gumrining Dwiastuti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Community empowerment is an important approach to enhancing community capacity and participation in addressing environmental health issues independently and sustainably. In Widodomartani, Ngemplak, household waste management, particularly organic waste, remains a challenge. Some residents dispose of organic waste on vacant land without prior treatment, while others still burn inorganic waste generated from daily activities. These practices may contribute to environmental pollution and health problems. One alternative solution to reduce organic waste generation is the use of biopore infiltration holes made from recycled gallon containers. Biopores function to increase soil water absorption and serve as a medium for organic waste decomposition. This community service program aimed to improve community knowledge and skills in waste management through the application of biopore technology using used gallon containers. The program was implemented through several stages, including problem identification, health education, community self-survey, and cadre training. Educational and participatory approaches were applied, with students serving as facilitators in delivering education and practical training to community cadres. This activity is expected to increase community awareness and independence in managing organic waste, thereby supporting the creation of a cleaner, healthier, and more sustainable environment.